Cover Picture: Remote C−H Activation of Quinolines through Copper‐Catalyzed Radical Cross‐Coupling (Chem. Asian J. 6/2016). Issue 6 (1st March 2016) - Xu, Jun; Shen, Chao; Zhu, Xiaolei; Zhang, Pengfei; Ajitha, Manjaly J.; Huang, Kuo‐Wei; An, Zhongfu; Liu, Xiaogang
Abstract : Controlling C−H functionalization reactions to produce any desirable products on demand is critical in chemical technology, but it seems extremely challenging in terms of site selectivity, especially at a position remote from catalytic centers. A copper‐catalyzed approach is now reported to allow for remote C−H activation at the C5 position of 8‐aminoquinoline. This remote functionalization protocol enables access to a broad range of sulfones without the need for organohalide precursors. More information can be found in the Full Paper by Pengfei Zhang, Kuo‐Wei Huang, Xiaogang Liu et al. onpage 882 in Issue 6, 2016 (DOI:10.1002/asia.201501407 ).